63.2k views
9 votes
Find the inverse

f(x)={e}^(3x - 1)
Tank you for your support ​

1 Answer

4 votes

Answer:


f^(-1)(x)=(1)/(3)(\ln x +1)

Explanation:

Given function:


f(x)=e^(3x-1)

Replace f(x) with y:


\implies y=e^(3x-1)

Take natural logs of both sides:


\implies \ln y = \ln e^(3x-1)

Apply the Power Log Law
\ln x^n=n\ln x :


\implies \ln y = (3x-1)\ln e

As
\ln e=1 then:


\implies \ln y = 3x-1

Rearrange to make x the subject:


\implies 3x=\ln y +1


\implies x=(1)/(3)(\ln y +1)

Swap x for
f^(-1)(x) and y for x:


\implies f^(-1)(x)=(1)/(3)(\ln x +1)

User Gawin
by
5.8k points